Application of Metal–Organic Frameworks in Multicomponent Reactions - Latifi, Younes; Behraveshfar, Mahdi; Teimouri, Mohammad Bagher (SynOpen, 2024)
Metal-catalyzed multicomponent reactions are versatile synthetic protocols often used to prepare a range of different products. These reactions provide complete molecular diversity and high atom efficiency while saving energy. Recently, metal–organic frameworks have attracted attention as environmentally friendly catalytic systems as they possess an abundance of catalytic sites in ordered crystal skeletons. In this graphical review, we highlight the recent progress made utilizing metal–organic frameworks to facilitate multicomponent reactions.
Keywords: metal–organic frameworks; multicomponent reactions; heterogeneous catalysis; transition-metal catalysts; organic linkers